2019
DOI: 10.1371/journal.pone.0210287
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mortality among HIV positive patients two years after completing recommended therapy for Cryptococcal meningitis in Uganda

Abstract: BackgroundCryptococcal meningitis (CCM) remains a leading cause of mortality amongst HIV infected patients in sub-Saharan Africa. When patients receive recommended therapy, mortality at 10 weeks has been reported to vary between 20 to 36%. However, mortality rate and factors affecting mortality after completing recommended therapy are not well known. We investigated mortality rate, and factors affecting mortality at 2 years among CCM patients following completion of recommended CCM therapy in Uganda.MethodsA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Similarly, our median (IQR) baseline CD4 cell count was high (327 (180-485)) compared to the best group in the study by Mberi et al of 87 [26]. Besides, patients with low CD4 cell counts are likely to be in WHO stage 3 or 4, a group prone to opportunistic infections and an elevated risk of mortality [36,37]. It is therefore possible that patients with lower CD4 cell counts in our study were bed ridden or died shortly after initiation of ART and were never reported to the HIV clinic.…”
Section: Plos Onesupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, our median (IQR) baseline CD4 cell count was high (327 (180-485)) compared to the best group in the study by Mberi et al of 87 [26]. Besides, patients with low CD4 cell counts are likely to be in WHO stage 3 or 4, a group prone to opportunistic infections and an elevated risk of mortality [36,37]. It is therefore possible that patients with lower CD4 cell counts in our study were bed ridden or died shortly after initiation of ART and were never reported to the HIV clinic.…”
Section: Plos Onesupporting
confidence: 59%
“…This is likely to make their continued engagement with the HIV clinic difficult. Such patients also have an increased risk of death especially in the first 6 months of ART due to severe immune reconstitution inflammatory syndrome and Cryptococcal meningitis [36,37]. It is therefore possible that they died shortly after starting ART and never reported to the ART clinic again.…”
Section: Plos Onementioning
confidence: 99%
“…CM is among the leading causes of mortality among adult HIV/AIDS patients in sub-Saharan Africa [42,43]. Early screening with cryptococcal antigen (CrAg) among the target population or advanced HIV-infected patients and giving pre-emptive treatment can prevent the development of CM and associated mortality.…”
Section: Cryptococcal Meningitismentioning
confidence: 99%
“…This might make their continued engagement with the HIV clinic hard. Such patients are further at an increased risk of death especially in the first 6 months of ART due to severe immune reconstitution inflammatory syndrome and Cryptococcal meningitis [34,35]. It is therefore possible that they could have died shortly after starting ART and were never reported to the ART clinic.…”
Section: Discussionmentioning
confidence: 99%